Effects of adding a low glycaemic index diet to a carbohydrate exchange dietary advice for women with gestational diabetes mellitus - Samiun, Nurul Alia Aqilah (2017)
Carbohydrate exchange (CE) or low glycaemic index (GI) dietary advice for women with gestational diabetes mellitus (GDM) produces comparable benefits. Whether adding a low GI diet to CE dietary advice would further enhance glycaemic control in women with GDM is unclear. This study investigated the effects of adding a low GI diet to the CE dietary advice on maternal glycaemia, metabolic outcomes, weight gain and dietary intake in women with GDM. This study employed a quasi-experimental study design conducted at Hulu Langat District Health Clinics. Four from the 12 clinics with the highest number of GDM cases were selected. Then, women with confirmed GDM at their second trimester from the two clinics were assigned to the CE alone (CE; n = 26). The other two were assigned to the intervention (addition of GI diet to the CE dietary advice) (LGI; n = 26). A simple random sampling were used when allocating the health clinics into it assigned group. The intervention performed at four visits similarly conducted for each group with the duration of intervention is 10 to 22 weeks. At baseline visit, similar CE dietary advice were given to each group by a research dietitian. Then, at visit 1, low GI dietary advice were given to the intervention group while the comparison group (CE) continues with the previous dietary plan. Maternal glycaemia (fasting blood glucose (FBG), glycated haemoglobin (HbA1c) and self-monitoring blood glucose (SMBG)) was a primary outcomes measure. The secondary outcome measures were maternal metabolic outcomes (blood pressure, high sensitivity C-reactive protein (hs-CRP) and insulin level), maternal weight gain and dietary intake.In this study, the response rate was 87% with 13% of attrition rate. The baseline characteristics were homogenous between LGI and CE group. Regarding primary outcome measures, no differences were observed for FBG and HbA1c between groups even though the HbA1c increased significantly in both groups over time (time effect; p < 0.05). The SMBG at pre-breakfast and post-breakfast were significantly lower in LGI than the CE group (group effect; p < 0.05). The SMBG at post-lunch were significantly reduced over time (time effect; p < 0.05) with no significant differences between groups. Regarding secondary outcome measures, the fasting insulin increased in both group, significantly higher in CE than LGI (group effect p < 0.05). Systolic blood pressure increased in LGI over time which on the other hand, reduced in CE group (time*group effect; p < 0.05). Other secondary outcomes did not differ significantly between groups. In dietary intake assessments, the energy, fat, dietary fibre, sugars, dietary GI and glycaemic load (GL) were significantly reduced in LGI than CE over time (time effect; p < 0.05) with no significant difference between groups. The sugars and dietary GI in LGI group reduced which on the other hand the dietary GI increased in CE (time*group effect; p < 0.05). LGI shows better adherence for fat and dietary GI intake compared to CE group (p < 0.05). In conclusion, adding a low GI to CE dietary advice improved SMBG at pre and post breakfast meal, and improve intake of energy, fat, dietary fibre, sugars, dietary GI and GL. However, the increase in systolic blood pressure warrants future investigation. The low GI dietary advice is feasible and well accepted among GDM women. Low GI can be added to a current advice to further improve the postprandial glycaemic management in GDM.